Modelo ambiental para una ciudad capital. (2013)
From a review of the various options for modeling a sustainable development in its environmental dimension; this research proposes a model of environmental impact for Bogota; using the Vensim PLE software to model the pollution; the pollution load and soil contamination. The model includes a limited number of endogenous variables; as well as a greater number of exogenous variables. This modeling allows us to anticipate the environmental situation in the capital; in order to support public policies for addressing issues such as economic sanctions and moral regulations on emissions; discharges and waste; environmental measures and environmentally friendly practices.